Management of Acute Renal Failure in Iraqi Children below 3 years - Malalla, Hoom S (Diyala Journal of Medicine, 2019)
Background: Acute renal failure is a clinical syndrome in which a sudden deterioration in renal function results in the inability of the kidneys to maintain fluid and electrolyte homeostasis. Objective: To study cases of acute renal failure in children below three years of age in respect to etiology, presentation, laboratory findings and management. Patients and Methods: A study of patients below 3 years of age with acute renal failure admitted at Al-No’man teaching hospital and were followed up in Pediatric Nephrology department in Al-Zahrawee hospital during the period from the 1st of October 2013 to the 1st of October 2015. Results: Forty patients with acute renal failure aging below three years old were included in this study. There were 29 (72.5%) male and 11(27.5%) female children giving male to female ratio of 2.6:1.Most common presentation was decreased urine output and acidotic breathing. Most common complication was seizure in 6(50%) cases. About 14(65.6%) cases needed peritoneal dialysis, 8( 34.4% ) cases responded to medical management, while8(15%) cases died. Conclusion: Acute renal failure in infants and young children below 3 years of age is not uncommon.It is a preventable disease because most cases are due to pre-renal causes. Prevention and rapid correction of severe dehydration may prevent acute renal failure and consequent complications and death.